Total richness of vascular plant species in an Andean forest of the Central Cordillera, Colombia - David-Higuita, Heriberto (2018)
Studies of plant diversity in tropical forests are usually restricted to trees or other groups of woody plants above a certain stem diameter. However, surveys that include all forms of live plants with no restrictions on their sizes, clearly indicate that non-woody plants are equally important. In this study, we reported the total species richness of vascular plants species (TSR) in one hectare plot in an Andean forest in Northwestern Colombia (6º 12' 48” N & 75º 29' 32” W). We evaluated the relative contribution of the different growth habits and the effect of the plant size, to TSR. We measured all individuals with diameter (D) ≥ 5 cm in the hectare and all the vascular plants of all sizes, including epiphytes, in a subsample of 0.25 ha. A total of 14 545 individuals distributed in 318 species, 72 families (considering Pteridophyta as one group) and 171 genera were registered. Most of the species showed a (D) < 10 cm (99.7%) and < 2.5 cm (94.4 %). The no-arboreal species (ground herbs, epiphytes and vines) represented 54.3 % of the total species reported in the plot, indicating that they are important in the structure, composition and species richness of this montane forest. Our results coincide with similar studies in other tropical forests. We concluded that to get a more detailed knowledge of the floristic diversity of a site, it is advisable to: 1) amplify the size range of the plants generally considered in the floristic inventories and 2) to include non-woody species. This information is crucial for making better decisions in local and global conservation efforts.